Apologies in a Legal Setting: Insights from Research into Injured Parties' Experiences of Apologies after an Adverse Event. Issue 1 (2nd January 2017) - Allan, Alfred; Carroll, Robyn
Abstract : There is scholarly support for the use of apologies in the settlement of legal disputes and anecdotal evidence of their effectiveness in mediation and other dispute resolution processes. There is also a growing body of empirical psychological research regarding the use and effectiveness of apologies available to inform and guide the practice of lawyers, mediators and other professionals, and judicial officers when apologies arise in legal proceedings. This article critically reviews the research literature concerning the experience of apology recipients and offers a framework for understanding the circumstances in which an apology may contribute to the resolution of a legal dispute.